Capacity Building Guru HIMPAUDI melalui Penerapan Deep Learning dalam Pembentukan Kesadaran Hukum Anak Usia Dini - Debrina Rahmawati; Alfan Bramantya; Dinna Eka Graha Lestari (Pusat Riset dan Inovasi Nasional, 2026)
Early childhood education is a crucial stage in the development of legal awareness and adherence to rules; however, teachers’ competence in fostering this awareness through a deep learning approach is still not optimal. A preliminary survey of early childhood education teachers revealed that the majority still rely on instructional and rote-learning methods, with limited understanding of deep learning as a reflective learning approach. This community service program aims to enhance the capacity of HIMPAUDI member teachers in Malang Regency to apply deep learning in fostering legal awareness among young children, particularly regarding compliance with rules. The methods used include outreach through the provision of educational materials, discussions, and the implementation of best practices in deep learning for fostering legal awareness in young children. The outcome of this program is an increase in the participants’ science and technology. This program successfully shifted teachers’ paradigms from an authoritative and rote-learning approach toward a participatory, reflective, and experience-based approach in fostering legal awareness in early childhood. Similar capacity-building programs are recommended for replication in other regions to ensure the sustainability of strengthening the pedagogical competencies of early childhood education (PAUD) teachers in Indonesia.